2014
DOI: 10.17219/acem/37075
|View full text |Cite
|
Sign up to set email alerts
|

Medical Complications and Patient Outcomes in Iranian Veterans with Spinal Cord Injury

Abstract: Background. Spinal cord injury [ScI] occurring in military veterans is a disabling and highly morbid event. Often the victims are young active males who sustain these injuries during military conflict and suffer from the complications of the ScI for the rest of their lives. Objectives. The aim of the study is to report the epidemiology of Iranian ScI veterans and their health related quality of life, medical complications and patient associated outcomes. Material and Methods. a cohort of 1984 patients was exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Ten articles were identified that reported the prevalence or incidence of PUs in community dwellers from 6 months to 20 years after injury. [24][25][26][27][28][29][30][31][32][33] Of note, very few of these study subjects were reported to have undergone SCI rehabilitation. These 10 papers reported a PU prevalence of 26.7-46.2%, mean of 35.2%.…”
Section: Resultsmentioning
confidence: 99%
“…Ten articles were identified that reported the prevalence or incidence of PUs in community dwellers from 6 months to 20 years after injury. [24][25][26][27][28][29][30][31][32][33] Of note, very few of these study subjects were reported to have undergone SCI rehabilitation. These 10 papers reported a PU prevalence of 26.7-46.2%, mean of 35.2%.…”
Section: Resultsmentioning
confidence: 99%
“…Persons with tetraplegia have increased medical needs, as noted by the greater prevalence urological conditions, pulmonary infections, diabetes, cardiovascular disease, constipation, osteoporosis, and skin breakdown. 14,[39][40][41][42][43][44] The impact of missing medical appointments, in persons who already have greater medical needs than typical able-bodied controls, may jeopardize optimal clinical care.…”
Section: Discussionmentioning
confidence: 99%
“…Survivors of spinal cord injury coexist with sequelae characterized by impairment of some vital functions, such as neurogenic dysfunction of the lower urinary tract, which may manifest as detrusor hyperactivity, detrusor sphincter dyssynergia, hypocontractile detrusor, sphincter insufficiency or bladder impairment (2) .…”
Section: Introductionmentioning
confidence: 99%